Complicated Neurotuberculosis with sinus venous thrombosis: A case-report. (2022) - Ali, Yousra; Imam, Yahia; Ahmedullah, Hasan S.; Akhtar, Naveed; Kamran, Saadat; Al Maslmani, Muna; Al Khal, A. Latif; Own, Ahmed; Deleu, Dirk
Abstract: Introduction: Neurotuberculosis comprises around 6% of systemic tuberculosis. It targets a younger population, and it often leads to severe neurological complications or death. Case report: We report a young gentleman with a clinically defined tuberculous meningitis (TBM) and multiple neurological complication associated with TBM occurring simultaneously. This includes hydrocephalus requiring a ventriculoperitoneal shunt, vasculitic infarcts, cranial nerve palsies, TB granuloma and cerebral venous thrombosis. The cerebrospinal fluid polymerase chain reaction for tuberculosis as well as cultures remained negative repeatedly. The patient was treated with anti-tuberculous medication in addition to steroids based on validated scoring systems suggestive of TBM and made a good recovery. Conclusion: This report highlights the different complication seen with TBM and the importance of using clinical criteria to guide management plan particularly when cultures are negative.